Answer:
First year = 30000
Second year = 12000
Step-by-step explanation:
Given
[tex]Loan = \$42000[/tex]
Represent first year with f and second year with s.
So, we have:
[tex]s + f = 42000[/tex]
and
[tex]f = 3s - 6000[/tex]
Required
Solve for f and S
Substitute 3s - 6000 for f in the first equation.
[tex]s + f = 42000[/tex]
[tex]s + 3s - 6000 = 42000[/tex]
[tex]4s - 6000 = 42000[/tex]
Collect Like Terms
[tex]4s = 42000 + 6000[/tex]
[tex]4s = 48000[/tex]
Solve for s
[tex]s = 48000/4[/tex]
[tex]s = 12000[/tex]
Substitute 12000 for s in [tex]f = 3s - 6000[/tex]
[tex]f = 3 * 12000 - 6000[/tex]
[tex]f = 36000 - 6000[/tex]
[tex]f = 30000[/tex]